Squamous metaplasia induced by transfection of human papillomavirus DNA into cultured adenocarcinoma cells. Issue 2 (1st April 2003) - Kinjo, T; Kamiyama, K; Chinen, K; Iwamasa, T; Kurihara, K; Hamada, T
Abstract : Background/Aim: It has been reported previously in cases of adenosquamous carcinoma of the lung in Okinawa, a subtropical island 2000 km south of mainland Japan, that the squamous cell carcinoma components were positive for human papillomavirus (HPV) by non-isotopic in situ hybridisation (NISH). The adenocarcinoma cells adjacent to the squamous cell carcinoma components were enlarged and also positive for HPV. This is thought to indicate that after adenocarcinoma cells are infected with HPV, they undergo morphological changes, and that "squamous metaplasia" follows. In this present study, the effects of HPV transfection into adenocarcinoma cells were examined. The relation between the region expressing the HPV gene and squamous metaplasia was also studied. Methods: Plasmid pBR322 containing HPV type 16 (HPV-16) was transfected into cultured colonic adenocarcinoma (DLD-1) and lung adenocarcinoma (PC-14) cells using the calcium phosphate method. Neomycin was used as a selection marker. The presence of HPV E1, E2, E4, E5, E6, E7, L1, and L2 mRNAs and also transglutaminase 1, involucrin, cyclin dependent kinases (CDKs), cyclins, caspases, apoptosis inducing factor, DNase γ, Fas, and Fas ligand mRNAs in HPV transfected cells was investigated by means of reverse transcription polymerase chain reaction (RT-PCR). The G0–G1 cell population was analysed by flow cytometry. Morphological examination under light and electron microscopes was also carried out. Results: The virus transfected cells showed squamous metaplasia when they were injected into severe combined immunodeficient mice, expressing the high molecular weight keratin (Moll's number 1 keratin) and involucrin molecules immunohistochemically, and involucrin and transglutaminase I mRNAs by RT-PCR. The squamous metaplasia was most conspicuous in the HPV transfected DLD-1 cell when compared with HPV transfected PC-14 cells. Squamous metaplasia was most clearly demonstrated in one HPV transfected DLD-1 cell clone, which expressed not only E2 but also E6–E7 fusion gene mRNA. Viral L1 mRNA expression was absent in HPV transfected cell clones, and was not related to squamous metaplasia. The growth rate of HPV transfected cells was reduced. Transfection of the virus into the cultured adenocarcinoma cells increased the G0–G1 cell population greatly, as assessed by flow cytometer analysis. Furthermore, in the virus transfected cells, apoptosis was also observed by means of the terminal deoxynucleotidyl transferase mediated dUTP biotin nick end labelling method. Conclusion: HPV transfection into adenocarcinoma cells induced clear squamous metaplasia. One of the HPV transfected cell clones that expressed E2 and E6–E7 fusion gene mRNA showed the squamous metaplasia particularly clearly, and apoptosis was also demonstrated.